Selection bias in studies with unequal allocation - Kuznetsova, Olga M. (Henry Stewart Talks, 2020)
Origins of selection bias in clinical trials, Blackwell-Hodges model for selection bias, Derivation of selection bias with unequal allocation, Directional guessing strategy, Directional guessing strategy with permuted block randomization, Directional strategy maximizes selection bias, Directional strategy with biasing threshold, Directional strategy with biasing threshold and large permuted blocks, Brick Tunnel Randomization, Undisclosed use of the Brick Tunnel Randomization reduces selection bias